Abnormal lipid metabolism in cancer-associated cachexia and potential therapy strategy - Fang, Ruoxin; Yan, Ling; Liao, Zhengkai (Frontiers in Oncology, 2023)
Cancer-associated cachexia (CAC) is a major characteristic of advanced cancer, associates with almost all types of cancer. Recent studies have found that lipopenia is an important feature of CAC, and it even occurs earlier than sarcopenia. Different types of adipose tissue are all important in the process of CAC. In CAC patients, the catabolism of white adipose tissue (WAT) is increased, leading to an increase in circulating free fatty acids (FFAs), resulting in “ lipotoxic”. At the same time, WAT also is induced by a variety of mechanisms, browning into brown adipose tissue (BAT). BAT is activated in CAC and greatly increases energy expenditure in patients. In addition, the production of lipid is reduced in CAC, and the cross-talk between adipose tissue and other systems, such as muscle tissue and immune system, also aggravates the progression of CAC. The treatment of CAC is still a vital clinical problem, and the abnormal lipid metabolism in CAC provides a new way for the treatment of CAC. In this article, we will review the mechanism of metabolic abnormalities of adipose tissue in CAC and its role in treatment.